Patency of the arterial pedal–plantar arch in patients with chronic kidney disease or diabetes mellitus. (May 2018) - Haine, Axel; Haynes, Alan G.; Limacher, Andreas; Sebastian, Tim; Saengprakai, Wuttichai; Fuss, Torsten; Baumgartner, Iris
Background: Patency of the pedal-plantar arch limits risk of amputation in peripheral artery disease (PAD). We examined patients without chronic kidney disease (CKD)/diabetes mellits (DM) [PAD-control], those with DM without CKD, and those with CKD without DM. Method: Uni- and multivariate logistic regression was used to assess association of CKD with loss of patency of the pedal–plantar arch and presence of tibial or peroneal vessel occlusion. Multivariate models adjusted for age, sex, hypertension, hyperlipidemia and smoking. Results: A total of 419 patients were included [age 75.2 ± 10.3 years, 288 (69%) male]. CKD nearly doubled the unadjusted odds ratio (OR) for loss of patency of the pedal–plantar arch. After adjustment, association remained significant for severe CKD [estimated glomerular filtration rate (eGFR) ≤ 29 ml/min compared with eGFR ≥ 60 ml/min, adjusted (adj.) OR 8.24 (95% confidence interval CI 0.99–68.36, p = 0.05)]. CKD was not related to risk of tibial or peroneal artery occlusion [PAD-control versus CKD, adj. OR 1.09 (95% CI 0.49–2.44, p = 0.83)] in contrast to DM [PAD–control versus DM, adj. OR 2.41 (95% CI 1.23–4.72, p = 0.01), CKD versus DM, adj. OR 2.21 (95% CI 0.93–5.22); p = 0.07)]. Conclusions: Below the knee (BTK) vascular pattern differs in patients with either DM or CKD alone. Severe CKD is a risk factor for loss of patency of the pedal–plantar arch.